2004
DOI: 10.1097/01.alc.0000145688.30448.2c
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Naltrexone in a Community Treatment Program

Abstract: These data suggest that naltrexone may offer particular benefit to patients who continue to drink during the early stages of the trial as compared with those who have achieved abstinence before treatment entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 22 publications
1
27
1
1
Order By: Relevance
“…The mean naltrexone adherence rate of 78% observed for the first four months of this treatment is generally very good considering the fact that this study was conducted in a real-world treatment setting. The adherence rate was better than in the study by Killeen et al [28] who reported an adherence rate of 51%. in a 12-week community treatment programme in which the patients were randomised to receive either 50 mg of naltrexone daily or placebo.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The mean naltrexone adherence rate of 78% observed for the first four months of this treatment is generally very good considering the fact that this study was conducted in a real-world treatment setting. The adherence rate was better than in the study by Killeen et al [28] who reported an adherence rate of 51%. in a 12-week community treatment programme in which the patients were randomised to receive either 50 mg of naltrexone daily or placebo.…”
Section: Discussioncontrasting
confidence: 67%
“…In a study by Killeen et al [28] that monitored the use of naltrexone (daily dose) in a community-based programme, the reported naltrexone adherence during the 12-week treatment was 51%. In order to broaden this field of research, the aim of this study was to examine patients' treatment adherence (percentage of drinking occurrences in which the patient used naltrexone) in an outpatient treatment environment for problem drinking that involved targeted use of naltrexone and cognitive behavioural therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of small to medium size studies (Volpicelli et Kiefer et al 2003Kiefer et al ,2004 and two large clinical trials (Garbutt 2005,Anton 2006) reported that naltrexone was effective in delaying relapse to heavy drinking, reducing the intensity of drinking or increasing percent days abstinence. Several systematic reviews indicated that naltrexone efficacy was associated with a small to moderate effect size (Garbutt et Killeen et al 2004) found no significant benefit associated with naltrexone treatment. Some meta-analyses also found no effect of naltrexone on abstinence (Garbutt et al 1999,Bouza et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study [80], 88 patients were randomised to one of 4 groups: paroxetine (40mg/d) or desipramine (200mg/d), with naltrexone (50mg/d) or placebo, but there was no significant difference in side effect reporting between groups. Several studies have included patients with co-morbid alcohol dependence psychiatric disorders [81][82][83]. None of these show significantly different side effect profiles from non-comorbid groups.…”
Section: Ptsd and Other Co-morbid Conditionsmentioning
confidence: 99%